Pelatihan dan Pendampingan Pengelolaan Kearsipan bagi Tata Usaha di Fakultas Agama Islam Universitas Muhammadiyah Lampung - Mawardi Mawardi; Ulil Albab (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to evaluate the effectiveness of training and mentoring programs for archive management targeting administrative staff at the Faculty of Islamic Studies, Universitas Muhammadiyah Lampung. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. Key informants included officials and administrative staff involved in archive management. The research identified supporting and inhibiting factors in program implementation and assessed its impact on staff competence enhancement. Findings revealed that the training positively contributed to improving participants' skills in archive classification, storage, and maintenance following national standards. Structural support and effective communication were identified as major supporting factors. However, challenges included limited facilities, low staff awareness, and a shortage of professional archivists. The study recommends sustainable mentoring, increased funding for facilities, and the adoption of digital archiving. These findings provide a foundation for developing more effective and adaptive training programs in higher education environments.